Identification of Risk Work Accident on The Making Process Tofu Study Case UD. Ainul Yaqin Wringinanom Gresik - Fitria, Aida; Nourma Rhomadhoni, Muslikha (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: In the process of making tofu, there is a risk of danger that causes work accidents and occupational diseases to occur. Hazard risks can occur from environmental factors and the workers themselves. Objective: Therefore, this study aims to identify a description of the risk of work accidents in the process of making tofu at UD. Ainul Yaqin. Method: This research is qualitative research while the data obtained from the results of observations and interviews. There were 6 informants involved in the study consisting of 1 supervisor and 5 workers. Data analysis using JSA method. Result and Discussion: The identification results show that there are 23 hazards in the process of making tofu at UD. Ainul Yaqin there are physical hazards, ergonomic hazards, biological hazards and chemical hazards. The risk assessment is categorized as very high 3, high 10, medium 7 and low 3. The control efforts provided are not fully based on the control hierarchy, namely elimination, substitution, engineering control, administrative and personal protective equipment (PPE). Conclusion: The conclusions from the results of the study indicate that there is a risk of slipping, falling, tripping, slipping, itching, minor injuries, hearing loss, eye irritation, physical fatigue and skeletal muscle disorders experienced by workers in the process of making tofu. The industry should improve the conditions of the work environment so as to minimize the occurrence of work accidents and occupational diseases.